Legumes as a factor in beef production - Loomis, George W. (My University, 1904)
Introduction: In recent years beef production has become more of an art than ever before. Those who now feed on the old plan, of one-half bushel of corn and a little of any kind of roughage per steer daily, are generally unsuccessful and soon go out of business. On the other hand, however, those who make a study of the various feeds, and make a wise choice in the feeds which they use, are receiving profitable returns. I am sure that the problem of successful steer-feeding cannot be solved except by the use of the legumes, in the feeding ration; for they form the cheapest source of the costly and necessary nutrient protein.
Citation: Loomis, George W. Legumes as a factor in beef production. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Vegetables; Nutrients; Beef Production; Factors Affecting Beef Production; Agriculture; Theses; Manuscripts (documents)